The voyage of the Fox in the Arctic seas : a narrative of the discovery of the fate of Sir John Franklin and his companions - M'Clintock, Francis Leopold, Sir, 1819-1907. (London : J. Murray, 1860)
Portion of author's autograph letter signed mounted on verso of front free endpaper. One folded map detailed to accompany author's narrative enclosed in rear end pocket. Spine title: Fate of Franklin and his discoveries. Mode of access: Internet.